ПРО ДЕЯКІ ВПЛИВИ СКЛАДУ ГЕНЕРУЮЧИХ ПОТУЖНОСТЕЙ НА ДИНАМІЧНІ ВЛАСТИВОСТІ ЕНЕРГОСИСТЕМ - Буткевич, О.Ф.; Гурєєва, Т.М.; Чижевський, В.В.; Юнєєва, Н.Т. (Інститут електродинаміки НАН України, Київ, 2022)
The analysis results of the composition changes' impact in the power systems' (PSs) generating capacities on natural frequencies and electromechanical transient processes in the PSs are given. The cases when specified changes are a consequence of the introduction of generation sources groups which will partially replace the generating capacities of thermal power plants were considered. In this research well-known test two-area (4-machine) and 6-machine PS schemes were used. References 10, figures 5, tables 3.